What satisfactions do self‐publishing authors gain from the process?. Issue 4 (1st October 2013) - BAVERSTOCK, Alison; STEINITZ, Jackie
ABSTRACT: This paper, a follow‐up to our previous Learned Publishing paper (http://dx.doi.org/10.1087/20130310 ), extends the reporting of new research into the motivations, demographics, processes, and outcomes of self‐publishing authors. The research findings challenge traditionally held notions about the lack of satisfaction in either the process or final product in self‐publishing. By contrast, the authors researched emerged as very satisfied with the process of self‐publishing, likely to do it again and recommend it to others – and these trends were observed across all the demographic categories and types of content. The generally high rate of republishing among the cohort can be taken as further evidence of associated satisfaction. The research offers conclusions that are relevant to all stakeholders in publishing and provides a foundation for more specific research within particular publishing sectors and roles.